Risk reducing mastectomy: outcomes in 10 European centres. Issue 4 (7th November 2008) - Evans, D G R; Baildam, A D; Anderson, E; Brain, A; Shenton, A; Vasen, H F A; Eccles, D; Lucassen, A; Pichert, G; Hamed, H; Moller, P; Maehle, L; et al.
Abstract : Background: Increasingly women at high risk of breast cancer are opting for risk reducing surgery. The aim of this study was to assess the effectiveness of this approach in women at high risk in both carriers and non-carriers of BRCA1/2 . Methods: Data from 10 European centres that offer a genetic counselling and screening service to women at risk were obtained prospectively from 1995. Breast cancer risks were estimated from life tables and a control group of women at risk who did not undergo surgery. Results: The combined centres have data on 550 women who have undergone risk reducing mastectomy with greater than 3334 women years of follow-up. Operations were carried out on women with lifetime risks of 25–80%, with an average expected incidence rate of 1% per year. No breast cancers have occurred in this cohort in the "at risk" unaffected breast, whereas >34 would have been expected. A high rate (2–3.6%) of occult disease was identified in the at risk breast at the time of surgery. Interpretation: We conclude that risk reducing surgery is highly effective.